Study on mechanical and microgeometric characteristics of ion-plasma deposited TiN coating on 40Cr steel substrate - Evgeniy V Sadyrin; Boris I. Mitrin; Leonid I. Krenev; Sergey M. Aizikovich (Advanced Engineering Research)
The ion-plasma sprayed titanium nitride (TiN) coating on the prepared 40Cr steel substrate is investigated. A part of the coating surface was covered by the copper foil mask to measure its thickness afterwards. The properties and characteristics of the sample surface microtopography before and after coating deposition are studied by the atomic-force microscopy (AFM). The technique for the high-precision determination of the coating thickness using the results of the AFM scanning of the transition area between the substrate and the coating on the sample surface is described and applied. The calculated uncertainty of the measured value of thickness is significantly less than in other methods. Mechanical properties of the coating are measured by the instrumental indentation method; the significance of an accurate determination of the correct thickness for measuring the coating characteristics by the indentation technique is shown.